Biorefinery options to valorize the spent liquor from sulfite pulping. Issue 12 (26th September 2014) - Rueda, Cristina; Calvo, Pedro A.; Moncalián, Gabriel; Ruiz, Gema; Coz, Alberto
Abstract BACKGROUND Spent sulfite liquor is a by‐product obtained in the process of manufacturing dissolving pulp by the acid sulfite method. A full physico‐chemical characterization of this waste has been developed in order to determine if it is susceptible to valorization by means of biorefinery processes. RESULTS The main components present in this spent liquor are sugars from hemicelluloses (25.9%), mainly xylose (18.2%) because hardwood is used as a raw material, and lignosulfonates (50.6%). Taking into account the results obtained, a literature search has been done in order to establish the biorefinery options for this lignocellulosic waste, giving lignosulfonates, xylitol, ethanol, polyhydroxybutyrate or polybutylene‐succinate, hydrogen and furfural as the best options. However, other compounds present in the liquor such as furans, acids and inorganic pollutants can complicate the valorization options. CONCLUSIONS Spent sulfite liquor can be a good feedstock for biomass based processes. This paper will be useful for future work regarding the potential biorefinery opportunities of the sulfite mill. © 2014 Society of Chemical Industry